2010
DOI: 10.4103/0019-5154.70666
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of non-infectious erythematous, papular and squamous lesions of the skin

Abstract: Background:Dermatopathologists base their diagnostic approach on the tissue reaction pattern. This study mainly includes the interpretation of two major tissue reaction patterns, the psoriasiform and the lichenoid reactions, with clinicopathological correlation.Aims:To analyze the spectrum of non-infectious erythematous papular and squamous lesions of the skin at our institute, study the age, sex and anatomic distribution pattern and classify the lesions into major categories; determine the incidence of each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 18 publications
13
19
0
Order By: Relevance
“…Lesions with epidermal changes were categorized into interface dermatitis (60 cases), psoriasiform dermatitis (58 cases), and spongiotic dermatitis (16 cases). Chaudhary et al 5 and D'Costa et al 6 reported a similar incidence of interface dermatitis to our study. The predominant histological features of hyperkeratosis, acanthosis, lichenoid infiltrate, and pigment incontinence were reported in this study, corroborated with the observations made by Hegde et al 7 In psoriasiform dermatitis, most histological features in the epidermis were similar to the findings reported by Raghuveer et al 8 Munro's microabscesses are not found in early lesions of psoriasis and were reported only in 6.9% cases in the present study.…”
Section: Papular/non-vb Lesionssupporting
confidence: 91%
“…Lesions with epidermal changes were categorized into interface dermatitis (60 cases), psoriasiform dermatitis (58 cases), and spongiotic dermatitis (16 cases). Chaudhary et al 5 and D'Costa et al 6 reported a similar incidence of interface dermatitis to our study. The predominant histological features of hyperkeratosis, acanthosis, lichenoid infiltrate, and pigment incontinence were reported in this study, corroborated with the observations made by Hegde et al 7 In psoriasiform dermatitis, most histological features in the epidermis were similar to the findings reported by Raghuveer et al 8 Munro's microabscesses are not found in early lesions of psoriasis and were reported only in 6.9% cases in the present study.…”
Section: Papular/non-vb Lesionssupporting
confidence: 91%
“…D'Costa et al noted positive correlation in 97.52% cases and a negative correlation in 2.48 % cases. 3 In the present study, histopathology confirmed diagnosis in 90% cases while histopathology gave diagnosis in 10% of the cases. Inaloez stated that the diagnostic rate increased up to 100% by the presence of clinical information and histological examination.…”
Section: Discussionsupporting
confidence: 55%
“…3 Henseler et al identified two ages of onset: type I occuring at or before the age of 40years in approximately 75% of the patients; and type II presenting after the age of 40years. 5 Gudjonsson et al stated that type I psoriasis is HLA-associated, while type II lacks HLA association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lichenoid lesions was the most common histopathological diagnosis reported in the present study (26%) followed by Hansen's disease (23.9%). In the study by Bharambhe et al 7 lichenoid lesions were commonest (46.57%) followed by psoriasis (19.88%). In the study by Singh et al, 27.9% of the cases were diagnosed as nonspecific dermatoses followed by granulomatous lesions (23.5%).…”
Section: Discussionmentioning
confidence: 99%